Estimating the replacement potential of Norwegian high-speed passenger vessels with zero-emission solutions. (October 2021) - Sundvor, Ingrid; Thorne, Rebecca Jayne; Danebergs, Janis; Aarskog, Fredrik; Weber, Christian
Highlights: A new model to estimate energy demand of Norwegian high-speed passenger vessels. The most likely candidates for zero-emission replacement were identified. Battery power is more suitable for vessels with short trips. Timetable and route changes are required for more vessels to be zero-emission. Findings can be used for further feasibility studies including route optimisation. Abstract: High-speed passenger vessels have high greenhouse gas emissions per passenger kilometre travelled and require optimizations to provide a role in a low carbon society. This article works towards this goal as a study of the potential for replacing high-speed passenger vessels with compressed hydrogen or battery electric zero emission solutions. To do this, a model was developed based on automatic identification system data to calculate energy use for the existing Norwegian fleet in 2018. Using modelled energy consumption and assuming a maximum battery weight or compressed hydrogen volume each vessel can carry, the most likely candidates for replacement were identified. Results showed that 51 out of 73 vessels are most suitable for hydrogen propulsion, with 12 also suitable for battery electric propulsion. However, timetable and route changes are required for more vessels to be suitable. Route optimisation studies are therefore required, along with further detailed feasibility studies of the identified candidates and infrastructure requirements.